2022
DOI: 10.3390/drones6090259
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indiana Unmanned Aerial System Crash Scene Mapping Program

Abstract: Many public safety agencies in the US have initiated a UAS-based procedure to document and map crash scenes. In addition to significantly reducing the time taken to document evidence as well as ensuring first responder safety, UAS-based mapping reduces incident clearance time and thus the likelihood of a secondary crash occurrence. There is a wide range of cameras used on these missions, but they are predominantly captured by mid-priced drones that cost in the range of $2000 to $4000. Indiana has developed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Earlier studies have shown that neither the use of RTK drones [40] nor the application of GCPs improved horizontal accuracy significantly [41], and the differences typically remined below 5 cm. This level of accuracy is satisfactory for road accident investigation [31] (also see calculation below in Section 3.4).…”
Section: Introductionmentioning
confidence: 91%
“…Earlier studies have shown that neither the use of RTK drones [40] nor the application of GCPs improved horizontal accuracy significantly [41], and the differences typically remined below 5 cm. This level of accuracy is satisfactory for road accident investigation [31] (also see calculation below in Section 3.4).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, for S 1 and S 2 , six ACVs have been considered connecting specific origin/destination pairs, and their shortest paths have been computed (Table 5). Additionally, a T g value has been assigned to fixed nodes, particularly for each scenario: ACV (1) and ACV (2) takes-off at the same time t 0 and T g1 = 0; ACV (3) and ACV (4) takes-off at time t 1 and T g2 = t 0 + T g(1,2) ; ACV (5) and ACV (6) takes-off at time t 2 and T g3 = t 1 + T g (3,4) . Table 6 reports a detailed analysis of the two scenarios over different periods of time…”
Section: Aerial Network Model Simulation Scenariomentioning
confidence: 99%
“…Nowadays, Unmanned Aerial Vehicles (UAVs) are employed in several fields [1,2], and for this reason Advanced Air Mobility (AAM), also known as Urban Air Mobility (UAM), is expected to turn into reality in the near future. Currently, there are UAV applications in different fields such as smart agriculture, emergency and detection of buildings, bridges and other objects [3][4][5][6]. Moreover, UAM services for passengers-performed by electric vertical take-off and landing (eVTOL) aircraft-and freight transport, or some other services such as medical aid, are under development [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Desai et al [ 6 ] reflected that depending on the magnitude of the accident, the time needed to collect effective measurements with these materials can range from 45 min to several hours. Similarly, Struble [ 7 ] noted that data collection using traditional techniques can slow traffic flow for hours as the accident scene is reconstructed.…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out by Desai et al [ 26 ], who compared RTK measurements using a GNSS receiver with those obtained from UAV-based mapping, the scale errors derived from the UAVs varied by three cm with respect to the shots taken using a GNSS receiver, which was the accepted threshold for use in public safety cases. This work demonstrates that the cartography obtained by UAVs is a viable option due to its accuracy, affordability and efficiency.…”
Section: Introductionmentioning
confidence: 99%